Electron and ionic transport in high-radioactive silicate alkali-earth glasses - Zhydkov, O. (Condensed Matter Physics, 2004)
The paper is devoted to the experimental study of electric transport in a
very special substance, namely alkali-earth glasses containing the noticeable
quantity (up to 10%) of dissolved irradiated uranium nuclear fuel and
its fission and daughter products as well. Such a high-radioactive product
was formed at the active stage of the well-known heavy nuclear accident
which occurred on Chornobyl NPP facility in 1986. The soft matter
behaviour was established by measuring the temperature dependence of
viscosity, where the glassy properties had been identified unambiguously.
Static electric conductivity temperature dependence was measured for
80 K–1000 K temperature interval. The transport processes connected with
thermal activation of electrons, hopping conductivity in the band tails and
variable range hopping (VRH) were identified. The band structure of such
glasses manifests the energy gap of 1.8–2.0 eV width, which formed due
to long-range order and wide band tails connected with horizontal disorder,
which, in its turn, may originate from numerous traps and internal radiation
damages. The latter makes it possible to identify the investigated matter
as devitrified glass. The distinguishing feature of such devitrified glasses
is low ionization energy for electrons, providing a high spatial density of
electron excitations in α -particle tracks, which leads to such a collective
phenomena as the so-called Coulomb explosion. Робота присвячена експериментальному вивченню електроперенесення в дуже особливій речовині, а саме в лужноземельних стеклах, що містять помітну кількість (до 10%) розчиненого опроміненого ядерного палива та продуктів його поділу і напрацьованих продуктів. Такий високорадіоактивний матеріал був сформований в перебігу активної фази загальновідомої тяжкої ядерної аварії, що відбулася на Чорнобильській АЕС 1986 року. Поведінку такої речовини як електроліту було вивчено шляхом вимірювання температурної залежності в’язкості, при цьому недвозначно було ідентифіковано властивості, характерні для стекол. Було виміряно температурну залежність статичної електропровідності в інтервалі температур 80 К–1000 К. Було ідентифіковано процеси перенесення шляхом термічної активації електронів, стрибкову провідність в хвостах зон та стрибкову провідність зі змінною довжиною стрибка. Зонна структура таких стекол виявляє наявність забороненої зони шириною 1.8–2.0 еВ, сформованої через наявність дальнього порядку, та широких хвостів зон через горизонтальний безлад, який, в свою чергу, може бути зумовлений численними пастками та радіаційними дефектами. Останнє дозволяє ідентифікувати досліджений матеріал як ситал. Визначною особливістю таких ситалів є низька енергія іонізації для електронів, що забезпечує значну просторову густину електронних збуджень в треках α-часток і спричиняє прояв такого колективного явища, як кулонівський вибух.